2018
DOI: 10.1155/2018/8465651
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation on the Relationship between MS Frequency Response and Coal and Gas Outburst

Abstract: Microseismic (MS) frequency response is an important part of high-efficiency data mining to achieve the aim of coal and gas outburst (CGOB) early warning. Based on the variation pattern of acoustic emission (AE) signal in the coal failure process, the experimental characteristics of MS activity and typical signals CGOB were obtained in this study. First, the AE behavior of coal failure experiment was studied, and an explanation of laws was provided as follows: the fracture behavior of coal sample exhibits cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…in mine, tunnel cavern, diversion tunnel of hydropower station, underground storage cavern, slope excavation, etc. For example, Zhu et al [8], Ding et al [9] and Wang et al [10] conducted experimental investigation on the MS frequency response before the coal and rock dynamic disasters, such as coal and gas outburst, mine rock and rock burst, and found that the frequency spectrum distribution of MS varied in the damage evolution process of coal and rock and frequency spectrum law can reflect the damage degree of coal or rock to some extent. He et al [11] used the MS frequency index and energy index to monitor mining disturbance and geological anomaly of the coal seam and this method could realize reliable detection of distribution characteristics of static load stress field in coal seam area.…”
Section: Introductionmentioning
confidence: 99%
“…in mine, tunnel cavern, diversion tunnel of hydropower station, underground storage cavern, slope excavation, etc. For example, Zhu et al [8], Ding et al [9] and Wang et al [10] conducted experimental investigation on the MS frequency response before the coal and rock dynamic disasters, such as coal and gas outburst, mine rock and rock burst, and found that the frequency spectrum distribution of MS varied in the damage evolution process of coal and rock and frequency spectrum law can reflect the damage degree of coal or rock to some extent. He et al [11] used the MS frequency index and energy index to monitor mining disturbance and geological anomaly of the coal seam and this method could realize reliable detection of distribution characteristics of static load stress field in coal seam area.…”
Section: Introductionmentioning
confidence: 99%